CLASSROOM RELATED TALKS: Conversation Analysis of Asian EFL learners - Nur Akmaliyah (Englisia: Journal of Language, Education, and Humanities, 2014)
In this paper, the author first records, transcribes, and then analyses a short extract from an English conversation among three graduate students with different cultural backgrounds. It aims to analyse several aspects of conversation analysis; turn-taking, topic change, preference organisation, listing, use of figurative language, face saving, breakdowns and repairs, and dysfluency. The data analysis shows that there is an interesting feature occurs concerning to overlapping during conversation. Moreover, dysfluency is also one of noticeable features which exist regularly during the conversation. However, the figurative language that is expected to emerge during talk among different cultural background cannot be figured out because the participants tend to avoid using such complex and idiomatic language structure.